2016
DOI: 10.11152/mu.2013.2066.182.bet
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three ultrasound based elastographic techniques in children and adolescents with chronic diffuse liver diseases.

Abstract: Non-invasive techniques for liver fibrosis assessment were developed for adults and recent researches tested their accuracy in children. The only validated elastographic method for non-invasive liver fibrosis evaluation in children is Transient Elastography (TE). The aim of our study was to investigate the feasibility of liver stiffness (LS) measurement in paediatric patients with chronic liver diseases by means of Acoustic Radiation Force Impulse Elastography (ARFI) and 2D-Shear Wave Elastography (2D-SWE), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
2
31
0
2
Order By: Relevance
“…Assessing the subgroup with SR > 70%, a significant correlation between TE and pSWE was found (Kappa correlation factor = 0.761, p = 0.001). Overall, 2D-SWE correlated with TE better than pSWE [24].…”
Section: Comparison Of Te Pswe and 2d-swementioning
confidence: 84%
“…Assessing the subgroup with SR > 70%, a significant correlation between TE and pSWE was found (Kappa correlation factor = 0.761, p = 0.001). Overall, 2D-SWE correlated with TE better than pSWE [24].…”
Section: Comparison Of Te Pswe and 2d-swementioning
confidence: 84%
“…By contrast, 2D‐SWE provides real‐time ultrasound images during LS and SS measurement, and the superiority of LS and SS measurement by 2D‐SWE for detecting portal hypertension compared with those by TE has been shown in adults with cirrhosis . Among children with chronic liver disease, the acceptable measurement rate for LS was 100% in 2D‐SWE, compared to 94.4% in TE . The reliability of SS as measured by 2D‐SWE for predicting portal hypertension in pediatric patients with chronic liver disease has not yet been sufficiently confirmed and direct comparison of the accuracy of SS for detecting EGV between 2D‐SWE and TE has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta‐analysis evaluating point SWE including patients with mixed chronic liver diseases reported accuracies of 0.84 for the diagnosis of substantial fibrosis, 0.89 for the diagnosis of severe fibrosis, and 0.91 for the diagnosis of liver cirrhosis . A recent study reported that 2D SWE showed a better correlation compared to point SWE in a pediatric population . The advantage of 2D SWE is highlighted by the fact that this ultrasound‐based elastographic method is integrated in an ultrasound machine that can be used for other examinations .…”
Section: Discussionmentioning
confidence: 99%